Bottom-up approach of teaching classical thermodynamics in the Faculty of Chemical and Natural Resources Engineering, UTM - Awang, Mariyamni; Mat, Ramli; Hassan, Onn (2005)

(untitled)
The Faculty consists of five departments that offer five bachelor of engineering programmes. The curricula of four of the programmes namely chemical, chemical bioprocess, chemical-polymer, chemical-gas, consist of the same core subjects. The petroleum engineering curriculum has the same thermodynamics subject as the other four but the core subjects are different. Loverude, Kautz, and Heron 2002 presented their work on the difficulty of teaching the first law of thermodynamics to physics students. The main problem was that students did not recognise the situation or system for which the first law of thermodynamics could be applied. In a sense, their problem was similar to ours where all the concepts given in the earlier topics were lost to the students when they have reached the application topics in the last part of the subject. The main characteristic of bottom-up approach is to first teach students the basic components of a system or concepts that increase in complexity. The final system is then taught after about 75 percent of the semester is over. Students often complained of how the simple systems or concepts did not help them very much to understand or be able to design the final system. Whale and Cravalho, 1999 dealt with the difficulty in transmitting thermodynamic principles by using two approaches. One approach was to use design projects such as a refrigerator to present the various thermodynamics topics and how those topics were applied. Another approach was more complicated in that the curriculum of the programme was modified to integrate a few subjects. We felt that improving the teaching technique for the bottom up approach or use the top down approach in the form of design projects was easier to implement. The programmes in FCNE do not by design end up producing graduates who work or design power plants, refrigeration units or any of the systems taught in classical thermodynamics. They also do not use the power cycles or cooling cycles in other subjects. While their grasp of the final application may not be good, much of the concepts or basic units taught in thermodynamics will be used by the students in other subjects of their programmes. Our paper examines the curricula of the programmes in the faculty and shows that the bottom-up teaching approach in classical thermodynamics is appropriate for our students.